2003
DOI: 10.1084/jem.20021845
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Is Required For Lipopolysaccharide-induced Tumor Necrosis Factor α Production

Abstract: Lipopolysaccharide (LPS), a product of Gram-negative bacteria, is potent mediator of tumor necrosis factor (TNF)α production by myeloid/macrophage cells. Inhibitors capable of blocking the signaling events that result in TNFα production could provide useful therapeutics for treating septic shock and other inflammatory diseases. Broad spectrum tyrosine inhibitors are known to inhibit TNFα production, however, no particular family of tyrosine kinases has been shown to be essential for this process. Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
4
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(188 citation statements)
references
References 45 publications
10
169
4
5
Order By: Relevance
“…We show that dasatinib inhibits the secretion of histamine and IL-6 from mast cells and basophils, as well as TNF-␣ secretion from U937 cells, all of which depend on the kinase activity of Btk (28,31). Dasatinib is an inhibitor with a broad specificity, also termed multitarget inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that dasatinib inhibits the secretion of histamine and IL-6 from mast cells and basophils, as well as TNF-␣ secretion from U937 cells, all of which depend on the kinase activity of Btk (28,31). Dasatinib is an inhibitor with a broad specificity, also termed multitarget inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the physiological consequences of Btk inhibition, we determined the impact of dasatinib on the secretion of TNF-␣ and IL-6, which were described to depended on Btk (28,31,32). Firstly, TNF-␣ release of vitamin D3-differentiated U937 cells was measured in the presence of different concentrations of dasatinib and imatinib.…”
Section: Mutation Of the Gatekeeper Residue In Itk Confers Sensitivitmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruton's tyrosine kinase is a critical tyrosine kinase in TLR4, TLR7 and TLR9 signaling for activating NF-kB. 81 miR-346 is strongly induced by LPS treatment and targets Btk mRNA in the synovial fibroblasts of rheumatoid arthritis patients. 82 Whether miR-346 targets Btk in macrophages needs to be further studied.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xymentioning
confidence: 99%
“…We have shown that Btk is recruited to the LPS receptor Toll-like receptor-4 (TLR4) where it is activated and is required for NFB activation (6). In addition, peripheral blood mononuclear cells (PBMCs) isolated from XLA patients have been shown to have impaired TNF␣ production induced by LPS (7).…”
mentioning
confidence: 99%